2013
DOI: 10.1007/s00125-013-3022-x
|View full text |Cite
|
Sign up to set email alerts
|

The novel chemokine receptor, G-protein-coupled receptor 75, is expressed by islets and is coupled to stimulation of insulin secretion and improved glucose homeostasis

Abstract: Aims/hypothesis Chemokine (C-C motif) ligand 5 (CCL5) acts at C-C chemokine receptors (CCRs) to promote immune cell recruitment to sites of inflammation, but is also an agonist at G-protein-coupled receptor 75 (GPR75), which has very limited homology with CCRs. GPR75 is coupled to Gq to elevate intracellular calcium, so we investigated whether islets express this receptor and whether its activation by CCL5 increases beta cell calcium levels and insulin secretion. Methods Islet CCL5 receptor mRNA expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 38 publications
1
59
1
Order By: Relevance
“…Liu et al, 2013) reported that isolated human and mouse islets express GPR75 and the chemokine CCL5 increases intracellular calcium levels via activation of GPR75 and suggested CCL5-mediated stimulation of insulin secretion is also a function of GPR75 activation. Binding of CCL5 to GPR75 was not confirmed in these studies (Ignatov, Robert, Gregory-Evans, & Schaller, 2006; B. Liu et al, 2013), however, it is possible that 20-HETE pairing with GPR75 interferes with CCL5-GPR75 binding and modulates CCL5 effect on insulin secretion.…”
Section: -Hete In Obesitymentioning
confidence: 70%
“…Liu et al, 2013) reported that isolated human and mouse islets express GPR75 and the chemokine CCL5 increases intracellular calcium levels via activation of GPR75 and suggested CCL5-mediated stimulation of insulin secretion is also a function of GPR75 activation. Binding of CCL5 to GPR75 was not confirmed in these studies (Ignatov, Robert, Gregory-Evans, & Schaller, 2006; B. Liu et al, 2013), however, it is possible that 20-HETE pairing with GPR75 interferes with CCL5-GPR75 binding and modulates CCL5 effect on insulin secretion.…”
Section: -Hete In Obesitymentioning
confidence: 70%
“…Islets were isolated from 10 to 12 weeks old male mice of the inbred C57BL/6 (C57; Charles River) and outbred Crl:CD1 (ICR) mice (Charles River) strains by collagenase digestion of the exocrine pancreas [16]. All animal procedures were carried out in accordance with the UK Home Office Animals (Scientific Procedures) Act 1986.…”
Section: Methodsmentioning
confidence: 99%
“…An example of this is the administration of salicylate to improve insulin sensitivity in different obese mouse and rat models [138,145,146]. However it should be noted that some models of insulin resistance will often exhibit a relative insulin deficiency and thus drugs with positive effects of on insulin secretion can even be beneficial in insulin resistant models [147,148].…”
Section: Models Of Insulin Resistancementioning
confidence: 96%